The Archival Series Concerning the Confiscation of Jewish Property Found in the Archives of the Prefecture of Venice - Santoro, Raffaele (Umanistica Digitale, 2019)
Introduction to the Workshop "Data Sharing, Holocaust Documentation and the Digital Humanities: Best Practices, Case Studies and Benefits."